Coercion and Violence in Mental Health Settings Causes, Consequences, Management - Hallett, Nutmeg; Whittington, Richard; Richter, Dirk.; Eneje, Emachi; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book aims to provide a state-of-the-art overview of the contexts, causes and treatments that relate to the reduction of coercion and the prevention of violence in mental health settings. The objective of this new edition in Open Access is to integrate theoretical explanations, empirical findings and practical solutions on the topic from many countries and diverse professional contexts. A large proportion of the text is concerned with practical and applied guidance for practitioners and others based on a clear understanding of conceptual and theoretical issues. Significantly enriched by the contributions of lived experience editors and co-authors, this edition brings authentic, new perspectives that deepen its relevance and impact. There is extensive use of case studies drawn from practice and the media to enliven the discussion. The scope of the book is intended to go beyond a reductionist medical/biological orientation on coercion and violence in mental health by integrating this within broader psychological and social frameworks. It includes new relevant contributions from nursing, psychology, psychiatry and sociology. The language of the book is clear and understandable to a broad audience whilst offering new knowledge for researchers and other specialists.
SECTION I. UNDERSTANDING.-1 Introduction -- 2 The culture of coercion -- 3 Biopsychosocial theories of aggression -- 4 The lived experience of coercion -- 5 User, carer and professionals$1 (Bexperiences of coercion -- 6 Responses to violence -- SECTION II. SURROUNDINGS -- 7 Physical -- 8 Safety and security in psychiatric clinical environments -- 9 Ward culture and atmosphere -- SECTION III. ASSESSING -- 10 Measurement and prevalence -- 11 Prediction of violence -- SECTION IV. PREVENTING AND MANAGING -- 12 Reducing involuntary admissions -- 13Organisational responses to aggression -- 14 Trauma-informed care -- 15 Aggression management training -- 16 De-escalation -- 17 Pharmacological management -- 18 Coercive measures -- 19 Alternatives to coercion -- 20 Post incident support -- 21 Conclusions.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Nursing; Psychiatry; Clinical psychology; Psychology; Clinical health psychology; Nursing; Psychiatry; Clinical Psychology; Behavioral Sciences and Psychology; Health Psychology